Does financial integration spur economic growth? : New evidence from the first era of financial globalization - Moritz Schularick; Thomas M. Steger (Center for Economic Studies and ifo Institute (CESifo), 2006)
Does international financial integration boost economic growth? The question has been discussed controversially for a long time. As of yet, robust evidence for a positive impact is lacking (Edison et al., 2002). However, there is substantial narrative evidence from economic history that highlights the contribution European capital made to economic growth of peripheral economies before 1914. We have compiled the first comprehensive data set to test this hypothesis. The main finding is that there was indeed a significant and robust growth effect. Our theoretical explanation stresses property rights protection as a prerequisite for the standard neoclassical model to work properly.
Keywords: F30; O16; O11; F21; N20; F15; N10; 330; international financial integration; economic growth; first era of globalization; Globalisierung; Internationaler Finanzmarkt; Marktintegration; Wirtschaftswachstum; Wirtschaftsgeschichte; Welt